La praefectura di Peltuinum e il suo territorio (ACME, 2020)
The ruins of the ancient Peltuinum were found about 30 km south-west of the present city of L’Aquila, on a plateau where the little villages of Prata d’Asidonia and San Pio delle Camere currently lie. It is an ancient settlement of the Vestini Cismontani, as Plinio called them in his description of the Italic land. Modern critics have mentioned this centre in several essays and references. It is part, in fact, of a hotly-debated topic: the praefecturae origins and their development after the Social War, specifically in non-urbanized or scarcely urbanized areas, and the administrative and juridical level of autonomy of the smaller centres (vici / fora / conciliabula) after the war. Representing an unusual or even emblematic example of how the Roman State annexed the italic land and how it was organised later on, it can be affirmed that Peltuinum history appears to be a key element when it comes to reconstructing the processes that led to the romanization of the central italic area. This paper is focused on the Peltuinum praefectura: starting with the debate about its origins, it first examines the relationship between the praefectura and the municipium during both the late Republican and the Imperial Age and, then, it brings into focus the connection between the centre and its vici, with specific attention to the vicus of Furfo.